2022
DOI: 10.1186/s42787-022-00144-z
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of the spread of COVID-19 in Plateau State, Nigeria

Abstract: In this research, a mathematical model consisting of non-pharmaceutical control measures is formulated. The developed model helps to examine the transmission of COVID-19 infection in Plateau State, Nigeria, using face masks$$c_{f}$$cfand social distancing$$c_{d}$$cdas control measures. Data used for the simulation of the developed model were obtained from Nigeria Centre for Disease Control which was fitted to the system of ordinary differential equations using nonlinear least squares method. Results at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…Five (5) of these articles were judged to be unrelated to the issue of crop prediction, while three (3) articles were found to be duplicates. As tabulated in Table 2, eleven (11) articles were found to be relevant for the identification of the hybrid time series models used to predict crops in general. Chi, (2021) [30] In the fifth stage, the study created a dataset (Appendix A) for hybrid time series models to predict crops.…”
Section: Narrative Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Five (5) of these articles were judged to be unrelated to the issue of crop prediction, while three (3) articles were found to be duplicates. As tabulated in Table 2, eleven (11) articles were found to be relevant for the identification of the hybrid time series models used to predict crops in general. Chi, (2021) [30] In the fifth stage, the study created a dataset (Appendix A) for hybrid time series models to predict crops.…”
Section: Narrative Reviewmentioning
confidence: 99%
“…The narrative review has revealed eleven (11) articles that have used the hybrid models to predict crops in general. Out of these articles, the study found seven (7) hybrid models, namely ARIMA-ANN, ARIMA-SVM, ARIMA-TDNN, ARIMA-NLSVR, ARIMAX-SVM, ARIMAX-ANN, and SARIMA-NARNN.…”
Section: Hybrid Models From Literaturementioning
confidence: 99%
See 2 more Smart Citations